KELAS LITERASI GEMBIRA: PENGEMBANGAN MINAT BACA SISWA SD MELALUI BUKU CERITA INTERAKTIF - Endang Setyowati; Kingkin Puput Kinanti; Ari Nugrahani; Harry Surahman (CV SWA Anugerah, 2025)
The reading interest of elementary school students in Indonesia is still relatively low. Many students have not yet developed an independent reading habit due to the limited availability of engaging and age-appropriate media. To address this issue, the “Joyful Literacy Class” program was developed as an initiative to foster reading interest through the use of interactive storybooks equipped with appealing illustrations and simple activities designed to encourage active student participation. The implementation method of this program employed a participatory approach, consisting of observation, media development, literacy class implementation, and evaluation. The results indicate an increase in students’ reading interest, reflected in higher reading frequency, enthusiasm during activities, and improved comprehension of story content. This program has proven effective in cultivating early reading habits and can serve as a model for enjoyable and easily applicable literacy learning in elementary schools.